Experimental Transmission of Plasmodium malariae to Anopheles gambiae. (4th July 2020) - Pinilla, Yudi T; Boussougou-Sambe, Stravensky T; Gräßle, Sarah; Ngossanga, Barclaye; Doumba-Ndalembouly, Ange G; Weierich, Andrea; Bingoulou, Gedeon; Malinga, Emma G; Nguiffo-Nguete, Daniel; Ntoumi, Francine; Djogbénou, Luc; Issifou, Saadou; et al.
Abstract: Our current knowledge of the clinical burden, biology, and transmission of Plasmodium malariae is extremely scarce. To start addressing some of those questions, we experimentally infected Anopheles gambiae mosquitoes with fresh P. malariae isolates obtained from asymptomatic individuals in Lambaréné, Gabon. The proportion of mosquitoes infected via direct membrane feeding assay with either P. malariae monoinfections (16% [19 of 121]) or coinfections (28% [31 of 112]) was higher after serum replacement than in parallel groups without serum replacement (4% [4 of 102] and 4% [2 of 45], respectively; P  < .01). Our results show that isolates from asymptomatic carriers can be used for experimental studies of P. malariae transmission. Abstract : Plasmodium malariae was experimentally transmitted in a colony of Anopheles gambiae sensu stricto mosquitoes using fresh parasite isolates obtained from asymptomatic individuals with microscopic and molecular evidence of P. malariae, either as monoinfections or as mixed infections.